THE IMPACT OF GREEN FINANCE ON BANKING PERFORMANCE IN INDONESIA - Yafie, Rafly Izaz Mada; Zuhroh, Idah; Anindyntha, Firdha Aksari (Jurnal Aplikasi Akuntansi, 2024)
Green Finance refers to financial practices that can be described through financial services and products that take environmental sustainability to support sustainable development. The role of green finance is to connect financial goals with the environment to encourage inclusive economic growth. One form of green finance implementation is in financial institutions, especially banking. This study aims to analyze the impact of green finance implementation in the banking sector on banking performance as proxied by the profitability ratio in the 2018-2022 period. The Generalized Method of Moments (GMM) dynamic panel is used. The Green Daily Operation (GDO) and Green Finance Policy (GFP) variables indicate the implementation of green finance in banking. Other independent variables use banking performance ratios consisting of the capital adequacy ratio, non-performing loans, and the bank's operational efficiency ratio. The study results show that green finance represented by implementing GFP can increase profitability, while GDO does not significantly affect banks' profitability in Indonesia. Furthermore, the internal banking ratio that is not significant to profitability is the capital adequacy ratio, while increasing non-performing loans and operational efficiency ratio significantly negatively impacts bank performance because it reduces profitability. This research supports applying the green concept in the banking sector to improve sustainable bank performance.